Protecting the Environment for Self-interested Reasons: Altruism Is Not the Only Pathway to Sustainability - De Dominicis, Stefano; Schultz, P. Wesley; Bonaiuto, Marino (Frontiers in Psychology, 2017)
Concerns for environmental issues are important drivers of sustainable and pro-environmental behaviors, and can be differentiated between those with a self-enhancing (egoistic) vs. self-transcendent (biospheric) psychological foundation. Yet to date, the dominant approach for promoting pro-environmental behavior has focused on highlighting the benefits to others or nature, rather than appealing to self-interest. Building on the Inclusion Model for Environmental Concern, we argue that egoistic and biospheric environmental concerns, respectively conceptualized as self-interest and altruism, are hierarchically structured, such that altruism is inclusive of self-interest. Three studies show that self-interested individuals will behave more pro-environmentally when the behavior results in a personal benefit (but not when there is exclusively an environmental benefit), while altruistic individuals will engage in pro-environmental behaviors when there are environmental benefits, and critically, also when there are personal benefits. The reported findings have implications for programs and policies designed to promote pro-environmental behavior, and for social science research aimed at understanding human responses to a changing environment.